Din eğitiminin bireyin arınma sürecine etkisi (tezkiye) ilahiyat fakültesi örneği - Şeyma, Ecertaş (My University, 2020)
Yaratılmışların en mükemmeli olan, Yüce Allah tarafından muhatabı olarak kabul edilmiş insan, modern anlayışın ihmal ettiği yönüyle, bedeninin ötesinde ilahi olanı tecrübe etme potansiyeline sahiptir. Fıtratına yerleştirilmiş olan bu potansiyel vahiyle buluştuğu zaman, birey yaratıcısıyla bağ kurma imkânı elde eder. Ancak insanın hem bu dünyasını hem de ahiretini mamur edecek olan bu bağın kurulması, modernite ve buna bağlı olarak bireyde meydana gelen yeni bilişler sebebiyle zorlaşmış görünmektedir. Bu anlamda, bireyin arınarak yeniden potansiyelinin farkına varması anlamında gerekli görülen tezkiye süreci, önce bireyin kirlerinden arınması sonrasında ise onun yaradılışı itibariyle sahip olduğu potansiyelini Kur’an’ın rehberliği ışığında yeniden inşa etme süreci olarak tarif edilebilir. Bireyin kişiliğini hakiki gerçekliğine kavuşturması yönüyle ele alınan tezkiye kavramı, İslami bir kimliğin oluşması için gerekli görülen her şeyi kapsayıcı bir özelliğe sahiptir. Din eğitimine sunabileceği imkânların ne olabileceğini ortaya koymayı amaçladığımız bu kavram, çalışmada özellikle yüksek din eğitiminin verildiği ilahiyat fakülteleri bağlamında sorgulanmaktadır. Bu sorgulamanın sağlam bir zemine oturabilmesi adına tezkiye kavramı birçok açıdan ele alınmış, ilahiyat fakültesi programlarının amaç içerik ve kazanımları bağlamında, din eğitiminde bu kavramın nasıl bir boşluğu dolduracağı sorusuna yanıt aranmıştır

The human who is the most perfect of creatures, accepted by Almighty Allah as His interlocutor, has the potential to experience the divine beyond his body, in the aspect neglected by modern understanding. When he meets this potential revelation, which is embedded in his nature, he gets the opportunity to bond with his creator. But the creation of this connection, which will bring about both this world and the hereafter of the human, seems to have been difficult due to modernity and the new cognitions that occur in the individual associated with it. In this sense, the purification process which is considered necessary in the sense of re-realizing the individual's own potential by purification can be described as a process of firstly becoming cleaned of his filths and then rebuilding the potential which he has due to his creation in the light of the Quran's guidance. The concept of purification, which is considered in the direction of bringing the individual's personality back to its true reality, has a feature that covers everything that is considered necessary for the formation of Islamic identity. This concept, which we aim to give religious education both a method and a purpose, is questioned in the study, especially in the context of the theological faculties where higher religious education is provided. In order for this question to sit on solid ground, the concept of purification has been considered in many ways, and the answer to the question of what kind of a gap it will fill in religious education in the context of the aims, content and attainments of the faculty of theology programs has been sought by analyzing the current situation.
Keywords: Arınma; Din; Din Eğitimi; Education; Eğitim; İlahiyat Tazkiya; Purification; Religion; Religious Education; Tezkiye; Theological Faculty